Thermosetting adhesive sheet and subgasket for fuel cells

The thermosetting adhesive sheet with polyurethane resin and crosslinking agent addresses sealing challenges in fuel cells by ensuring stable adhesion and resistance to high humidity, enabling room temperature storage and immediate bonding without curing, thus preventing defects.

JP7606717B2Active Publication Date: 2024-12-26HIGASHIYAMA FILM CO LTD +1

Patent Information

Application Number
JP2023544075
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-03-01
Filing Date
2023-02-21
Publication Date
2024-12-26
Estimated Expiration
2043-02-21

AI Technical Summary

Technical Problem

Existing adhesive materials for fuel cells face challenges in maintaining high sealing performance under high temperature and high humidity conditions, requiring lengthy heat-press bonding and potential heat damage, while also needing to be stored at low temperatures before use.

Method used

A thermosetting adhesive sheet with a polyurethane resin and crosslinking agent, having specific gel fraction, storage modulus, and glass transition temperature ranges, allowing for room temperature storage and immediate adhesion without curing, and resistance to high humidity environments.

Benefits of technology

The adhesive sheet achieves stable adhesion without curing, preventing defects like lifting, peeling, and voids in high temperature and humidity conditions, facilitating easy handling and use in fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007606717000002
    Figure 0007606717000002
  • Figure 0007606717000003
    Figure 0007606717000003
  • Figure 0007606717000001
    Figure 0007606717000001
Patent Text Reader

Abstract

The present invention provides: a thermosetting adhesive sheet which can be stored at room temperature and completes bonding without requiring a curing process after thermal compression bonding, while being capable of suppressing bonding defects such as lifting, separation and voids after the bonding even in a high-temperature high-humidity environment; and such a sub gasket for fuel cells. The present invention provides a thermosetting adhesive sheet 10 that is used for the purpose of sealing the periphery of an electrolyte membrane-electrode structure, which is obtained by arranging electrodes on both sides of a solid polymer electrolyte membrane, of a fuel cell. This thermosetting adhesive sheet 10 comprises an adhesive layer 14 which is formed of a cured product of an adhesive composition that contains a polyurethane resin having a reactive functional group and a crosslinking agent; the adhesive layer 14 has a gel fraction of 60% by mass or more; the storage elastic modulus (G'100) at 100°C of the adhesive layer 14 is 5.0 × 104 Pa to 1.0 × 108 Pa; and the decrease rate of the storage elastic modulus (G'120) at 120°C relative to the storage elastic modulus (G'100) at 100°C is 0.5 or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermosetting adhesive sheet used to seal the periphery of a membrane electrode assembly (MEA) in which electrodes are arranged on both sides of a solid polymer electrolyte membrane of a fuel cell, and to such a subgasket. [Background technology]

[0002] In recent years, fuel cells have been attracting much attention as a means of suppressing global warming and environmental destruction, and as a next-generation power generation system, and research and development into them is being actively carried out. Fuel cells generate energy through an electrochemical reaction between hydrogen and oxygen, and examples of such fuel cells include phosphoric acid fuel cells, molten carbonate fuel cells, solid oxide fuel cells, and polymer electrolyte fuel cells. Among these, polymer electrolyte fuel cells are attracting attention as a power source for automobiles (two-wheeled and four-wheeled vehicles) and portable power sources, because they can be started up at room temperature, are small in size, and have high output.

[0003] In a polymer electrolyte fuel cell, the fuel gas supplied to the anode, for example, a gas mainly containing hydrogen (hereinafter also referred to as hydrogen-containing gas), is ionized on an electrode catalyst, and the hydrogen moves to the cathode through a solid polymer electrolyte membrane. The electrons generated at the anode are taken out to an external circuit and used as direct current electrical energy. An oxidant gas, for example, a gas mainly containing oxygen or air (hereinafter also referred to as oxygen-containing gas), is supplied to the cathode, and the hydrogen ions react with the oxygen molecules that have received the electrons to produce water.

[0004] The fuel cell has a stack structure in which many cells are stacked. The cell stack includes an electrode assembly (MEA) having an electrolyte membrane and electrodes, separators that sandwich the electrode assembly, and sealants (gaskets, subgaskets) for sealing the periphery of the electrode members and between adjacent separators. As such a sealant, for example, a hot melt adhesive is known, such as that disclosed in Patent Document 1. As a sealant other than a hot melt adhesive, for example, Patent Document 2 discloses an adhesive sheet using an adhesive resin composition containing a crystalline polyester resin and an amorphous polyester resin. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2019 / 216402 [Patent Document 2] Patent Publication No. 2015-017237 Summary of the Invention [Problem to be solved by the invention]

[0006] When a fuel cell is used, a sealing material such as an adhesive sheet is exposed to a high-temperature and high-humidity environment. It is desired to maintain high sealing properties even in such an environment. In addition, when forming a cell stack while sealing a specific portion of the MEA with an adhesive sheet, it is preferable that the handling of the adhesive sheet and the bonding operation can be easily performed. However, the sealing material of Patent Document 1 is a hot melt adhesive, and in the bonding process with the MEA, it is necessary to press the adhesive sheet at high temperature for a long time, so that the bonding operation takes a long time and there is a risk of thermal damage to the MEA during the bonding operation. In addition, the adhesive sheet of Patent Document 2 is capable of low-temperature bonding, but it is usually necessary to store or transport it at low temperature in order to keep it in an uncured or semi-cured state until the bonding process after the sheet is formed. In addition, after the bonding process, a curing process such as heat treatment or aging is required.

[0007] The object of the present invention is to provide a thermosetting adhesive sheet which can be stored at room temperature, which completes adhesion after heat and pressure bonding without going through a curing treatment process, and which, after adhesion, can suppress adhesion defects such as lifting, peeling, and voids even when placed in a high-temperature, high-humidity environment, and a subgasket for a fuel cell using such a thermosetting adhesive sheet. [Means for solving the problem]

[0008] In order to solve the above problems, the thermosetting adhesive sheet according to the present invention is a thermosetting adhesive sheet used to seal the periphery of a membrane electrode assembly in which electrodes are disposed on both sides of a solid polymer electrolyte membrane of a fuel cell, the thermosetting adhesive sheet having an adhesive layer formed from a cured product of an adhesive composition containing a polyurethane resin having a reactive functional group and a crosslinking agent, the adhesive layer having a gel fraction of 60 mass % or more and a storage modulus at 100°C (G' 100 ) is 5.0 × 10 4 Pa or more 1.0×10 8 The storage modulus (G') at 100°C is 100 ) versus storage modulus at 120°C (G' 120 ) decline is 0.5 or less.

[0009] Here, the adhesive layer may have a glass transition temperature of -10°C or more and 100°C or less. The adhesive layer may have a glass transition temperature of 50°C or more. The reactive functional group may include a carboxy group, and the crosslinking agent may include a multifunctional epoxy crosslinking agent. The ratio (b / a) of the molar amount (a) of the carboxy group of the polyurethane resin to the molar amount (b) of the epoxy group of the epoxy crosslinking agent may be 1.0 or more and 10.0 or less.

[0010] The adhesive layer is preferably formed on one surface of a base film, and the base film is preferably a film made of at least one resin material selected from the group consisting of polyarylate, polyethylene terephthalate, polyethylene naphthalate, polyamide, polyimide, polyphenylene sulfide, polysulfone, polyether sulfone, polyether ether ketone, and polyarylate. The thermosetting adhesive sheet further has a second base film on the surface of the adhesive layer opposite to the surface on which the base film is provided, and the second base film is preferably a film made of at least one resin material selected from the group consisting of polyarylate, polyethylene terephthalate, polyethylene naphthalate, polyamide, polyimide, polyphenylene sulfide, polysulfone, polyether sulfone, polyether ether ketone, and polyarylate.

[0011] The subgasket for a fuel cell according to the present invention comprises a thermosetting adhesive sheet having the above-mentioned adhesive layer formed on one surface of a substrate film. Effect of the Invention

[0012] The thermosetting adhesive sheet according to the present invention has an adhesive layer with the above-mentioned specific material composition and physical properties, and therefore has excellent storage stability, can complete adhesion without a curing process after heat and pressure bonding, and can suppress adhesion defects such as lifting, peeling, voids, etc. even when placed in a high-temperature and high-humidity environment. Therefore, the thermosetting adhesive sheet can be suitably used as a sealant for fuel cells.

[0013] Here, when the glass transition temperature of the adhesive layer is -10°C or more and 100°C or less, the adhesive layer has good adhesion, and furthermore, adhesion defects such as lifting, peeling, and voids under high temperature and high humidity environments can be effectively suppressed. In addition, foreign matter attached to the adhesive layer can be easily removed. Furthermore, when the glass transition temperature of the adhesive layer is 50°C or more, the adhesive layer is likely to maintain high adhesion even under high temperature and high humidity conditions.

[0014] Furthermore, when the reactive functional group contains a carboxy group and the crosslinking agent contains a polyfunctional epoxy crosslinking agent, the reactivity of the polyurethane resin with the crosslinking agent increases.

[0015] When the ratio (b / a) of the molar amount (a) of the carboxyl group of the polyurethane resin to the molar amount (b) of the epoxy group of the epoxy crosslinking agent is 1.0 or more and 10.0 or less, a high crosslink density is obtained in the adhesive layer, and a suitable storage modulus is easily achieved. In addition, the adhesive layer has high adhesion to the adherend.

[0016] When the adhesive layer is formed on one side of the base film and the base film is a film made of the above-mentioned specified resin material, the thermosetting adhesive sheet becomes easier to handle, making it easier to carry out processes such as placement on an MEA.

[0017] In addition, when the thermosetting adhesive sheet further has a second base film on the side of the adhesive layer opposite to the side on which the base film is provided, and the second base film is a film made of the above-mentioned specified resin material, both sides of the adhesive sheet are covered with the base film and the second base film, so that the thermosetting adhesive sheet is particularly easy to handle. Even if foreign matter adheres to the sheet, it can be easily removed.

[0018] The subgasket for fuel cells according to the present invention includes a thermosetting adhesive sheet having the above-mentioned adhesive layer formed on one side of a base film. The adhesive layer constituting the above-mentioned thermosetting adhesive sheet has a predetermined material composition and physical properties, so that the subgasket for fuel cells has excellent storage stability, can complete adhesion after heat and pressure bonding without going through a curing treatment process, and can suppress adhesion defects such as lifting, peeling, and voids even when placed in a high-temperature and high-humidity environment. [Brief description of the drawings]

[0019] [Figure 1] FIG. 1 is a perspective view of a thermosetting adhesive sheet according to a first embodiment of the present invention. [Diagram 2]FIG. 2 is a perspective view of a thermosetting adhesive sheet according to a second embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The thermosetting adhesive sheet and the subgasket for a fuel cell according to an embodiment of the present invention will be described below. Unless otherwise specified, the various physical properties are values ​​measured at room temperature (about 23° C.) in the air.

[0021] <Configuration of thermosetting adhesive sheet> Fig. 1 is a perspective view of a thermosetting adhesive sheet (hereinafter sometimes simply referred to as adhesive sheet) 10 according to a first embodiment of the present invention. As shown in Fig. 1, the adhesive sheet 10 according to the first embodiment of the present invention has a base film 12 and an adhesive layer 14 formed on the surface of the base film 12. The adhesive layer 14 is exposed on the outermost surface of the adhesive sheet 10 as a whole. An opening W1 is provided in the center of the adhesive sheet 10 as a through-hole-like region. The adhesive sheet 10 is used together with a membrane electrode assembly (MEA) in which electrodes are disposed on both sides of an electrolyte membrane, and is used as a sealant that seals the periphery of the MEA.

[0022] <Base film> The specific configuration of the base film 12 is not particularly limited. Examples of the base film 12 include a polymer film and a glass film. The thickness of the base film 12 is not particularly limited, but is preferably within a range of 12 μm to 500 μm from the viewpoint of handling. More preferably, the thickness of the base film 12 is 38 μm or more, or 50 μm or more, and is 200 μm or less, or 100 μm or less. Note that the term "film" generally refers to a film having a thickness of less than 0.25 mm, but even if the thickness is 0.25 mm or more, it is included in the "film" as long as it is flexible.

[0023] When the base film 12 is a polymer film, examples of the polymer material constituting the base film 12 include polyester resins such as polyethylene terephthalate resin, polybutylene terephthalate resin, polyethylene naphthalate resin, and liquid crystal polyester, polycarbonate resin, poly(meth)acrylate resin, polystyrene resin, polyamide resin, polyphthalamide resin, polyimide resin, polyacrylonitrile resin, polypropylene resin, polyethylene resin, polyolefin resins such as polycycloolefin resin and cycloolefin copolymer resin, polyphenylene sulfide resin, polyvinyl chloride resin, polyvinylidene chloride resin, polyvinyl alcohol resin, polyvinylidene fluoride resin, fluorine resin, silicone resin, polysulfone resin, polyethersulfone resin, polyetheretherketone resin, and polyarylate resin. The polymer material of the base film 12 may be composed of only one of these, or may be composed of a combination of two or more of them by lamination or the like. Among these, from the viewpoints of heat resistance, mechanical properties, and the like, polyarylate, polyethylene terephthalate, polyethylene naphthalate, polyamide, polyimide, polyphenylene sulfide, polysulfone, polyethersulfone, polyetheretherketone, and polyarylate resins are preferred, and it is preferable that the base film 12 is made of at least one resin material selected from the group consisting of these resins.

[0024] The base film 12 may be composed of a single layer containing one or more of the above-mentioned polymeric materials, or may be composed of two or more layers, such as a layer containing one or more of the above-mentioned polymeric materials and a layer containing one or more of a different polymeric material.

[0025] <Adhesive layer> The adhesive layer 14 is formed from a cured product of an adhesive composition containing a polyurethane resin having reactive functional groups and a crosslinking agent. The adhesive composition has thermosetting properties, and the adhesive sheet 10 having the adhesive layer 14 functions as a thermosetting adhesive sheet. In the adhesive sheet 10 before use, the adhesive layer 14 is cured with some uncured material remaining (semi-cured state), and when adhering to an adherend, the adhesive layer 14 is further cured by heating, so that it can be used as a thermosetting adhesive sheet. In this specification, the concept of adhesion includes a form having tackiness, i.e., pressure-sensitive adhesion.

[0026] (Characteristics of the adhesive layer) From the viewpoint of ensuring adhesion, the thickness of the adhesive layer 14 is preferably 1 μm or more, more preferably 5 μm or more, whereas from the viewpoint of reducing the size of the fuel cell, the thickness of the adhesive layer 14 is preferably 50 μm or less, more preferably 25 μm or less.

[0027] The gel fraction of the adhesive layer 14 is 60% by mass or more. If the gel fraction is 60% by mass or more, in the bonding step with the MEA, the bonding can be completed without going through a curing treatment step after thermocompression bonding. In addition, the adhesive layer 14 has excellent storage stability, and even if placed in a high-temperature and high-humidity environment, adhesion defects such as lifting, peeling, and voids can be suppressed. Furthermore, the adhesive layer 14 can be stably stored at room temperature without low-temperature storage to maintain an uncured or semi-cured state until the bonding step. The gel fraction is preferably 65% ​​by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more, with the upper limit being 100% by mass.

[0028] The shear storage modulus (G') of the adhesive layer 14 at 100°C 100 ) is 5.0 × 10 4 Pa or more. 5.0×10 4 If the adhesive layer 14 has a hardness of 1.0 Pa or more, the adhesive layer 14 is appropriately cured even before the heat and pressure bonding, and therefore the adhesion can be completed with a short pressure bonding time. 100 is preferably 7.0 x 10 4Pa or more, more preferably 1.0×10 5 Pa or more. Also, G' 100 is 1.0 × 10 8 Pa or less. 1.0×10 8 If the elasticity of the adhesive layer 14 is less than or equal to G' Pa, the adhesive layer 14 can maintain its elasticity even at high temperatures, and therefore the adhesiveness can be improved. 100 is preferably 1.0 x 10 7 Pa or less, more preferably 5.0×10 6 Pa or less.

[0029] The storage modulus (G') of the adhesive layer 14 at 100°C 100 ) versus storage modulus at 120°C (G' 120 ) is 0.5 or less. If this rate of decrease is 0.5 or less, adhesion defects such as lifting, peeling, voids, etc. can be suppressed even when the adhesive layer 14 is placed in a high-temperature and high-humidity environment. From the viewpoint of further enhancing this effect, the rate of decrease is preferably 0.48 or less, more preferably 0.45 or less, and even more preferably 0.3 or less. There is no particular lower limit for the rate of decrease, but it is usually -0.1 or more, and preferably 0 or more. The rate of decrease is (G' 100 -G' 120 ) / G' 100 It can be calculated using the following formula.

[0030] The shear storage modulus (G') of the adhesive layer 14 at 120°C 120 ) is 5.0 × 10 4 Pa or more. 5.0×10 4 If the adhesive strength is 0.01 Pa or more, the adhesive strength is easily maintained even in a high temperature environment, and the adhesive strength is excellent in moisture and heat resistance. 120 is preferably 7.0×10 4 Pa or more, more preferably 1.0×10 5 Pa or more. Also, G' 120 is 1.0 × 10 8 It is preferable that the pressure is 1.0×10 Pa or less. 8If the elasticity of the adhesive layer 14 is less than or equal to G' Pa, the adhesive layer 14 can maintain its elasticity even at high temperatures, and therefore the adhesiveness can be improved. 120 is preferably 1.0×10 7 Pa or less, more preferably 5.0×10 6 Pa or less.

[0031] The glass transition temperature of the adhesive layer 14 is preferably -10°C or higher. If the glass transition temperature is -10°C or higher, adhesion defects such as lifting, peeling, and voids can be effectively suppressed even in a high-temperature and high-humidity environment, and foreign matter attached to the adhesive layer 14 can be easily removed. From this viewpoint, the glass transition temperature is more preferably -8°C or higher, and even more preferably -5°C or higher, and from the viewpoint of maintaining high adhesion even in a high-temperature and high-humidity environment, it is particularly preferably 50°C or higher. On the other hand, the glass transition temperature is preferably 100°C or lower. If the glass transition temperature is 100°C or lower, the adhesion to the MEA can be particularly good. From this viewpoint, the glass transition temperature is more preferably 95°C or lower, and even more preferably 90°C or lower.

[0032] The adhesive strength of the adhesive layer 14 to the base film 12 and the MEA at 23°C is preferably 1 N / 25 mm or more, more preferably 1.2 N / 25 mm or more, and even more preferably 2 N / 25 mm or more. If the adhesive strength is 1 N / 25 mm or more, lifting or peeling of the adhesive layer 14 can be suitably suppressed. There is no particular upper limit to the adhesive strength, but it is usually 50 N / 25 mm or less, or 40 N / 25 mm or less. The adhesive strength of the adhesive layer 14 may be evaluated by the same method as that for measuring the "initial peel strength" in the examples described later.

[0033] (Polyurethane resin) The adhesive composition constituting the adhesive layer 14 contains a polyurethane resin having a reactive functional group, as described above. By using a polyurethane resin, the adhesive layer 14 has appropriate flexibility and resistance to moist heat, and can be bonded by heating and pressing in a short time. Polyurethane resin is a general term for compounds containing two or more urethane bonds in one molecule. Polyurethane resin has a structure obtained by polymerizing polyisocyanate and polyol.

[0034] The polyisocyanate may have two or more isocyanate groups in one molecule, and from the viewpoint of the physical properties of the adhesive layer 14, diisocyanate or triisocyanate is preferable, and diisocyanate is more preferable. The diisocyanate may be appropriately selected from aliphatic diisocyanates such as hexamethylene diisocyanate and aromatic diisocyanates such as benzene-1,3-diisocyanate, taking into consideration the physical properties of the adhesive layer 14. The polyisocyanate may be used alone or in combination of two or more. In addition, an isocyanate-terminated prepolymer obtained by reacting a polyol with an excess of polyisocyanate may be used as an intermediate of a polyurethane resin.

[0035] The polyol may be any polyol having two or more hydroxyl groups in one molecule, and is preferably a diol or triol, more preferably a diol, from the viewpoint of the physical properties of the adhesive layer 14. The diol may be appropriately selected from aliphatic diols such as ethylene glycol and aromatic diols such as benzene diol, taking into consideration the physical properties of the adhesive layer 14. The polyol may be used alone or in combination of two or more. Also, prepolymers such as polyether polyol, polyester polyol, and polycarbonate polyol may be used.

[0036] The polyurethane resin may be a polyurethane urea resin further having a urea bond. The polyurethane urea resin has a structure in which, for example, a urethane resin having an isocyanate group at the end is bonded to a polyamine. The polyamine may have two or more amino groups in one molecule, and from the viewpoint of the physical properties of the adhesive layer 14, a diamine or triamine is preferable, and a diamine is more preferable. The diamine may be appropriately selected from known aliphatic diamines such as ethylenediamine and known aromatic diamines such as phenylenediamine, taking into consideration the physical properties of the adhesive layer 14. The polyamine may be used alone or in combination of two or more kinds.

[0037] The weight average molecular weight (Mw) of the polyurethane resin is preferably 5,000 or more, more preferably 10,000 or more, and even more preferably 50,000 or more. On the other hand, Mw is preferably 1,000,000 or less, more preferably 500,000 or less, and even more preferably 200,000 or less. If Mw is 5,000 or more, the moist heat resistance of the adhesive layer 14 can be improved, and if it is 1,000,000 or less, the coating workability of the adhesive composition becomes better.

[0038] The reactive functional group of the polyurethane resin is not particularly limited as long as it is a functional group capable of reacting with a crosslinking agent to form a bond, and examples thereof include hydroxyl group, phenolic hydroxyl group, methoxymethyl group, carboxyl group, amino group, epoxy group, oxetanyl group, oxazoline group, oxazine group, aziridine group, thiol group, isocyanate group, blocked isocyanate group, blocked carboxyl group, and silanol group. The polyurethane resin may contain one or more of these reactive functional groups. Among these, hydroxyl group, carboxyl group, amino group, and epoxy group are particularly preferred, and carboxyl group is more preferred from the viewpoint of availability and reactivity with the crosslinking agent. In the polyurethane resin, the reactive functional group may be directly bonded to the polyurethane chain, such as a polyol moiety, or may be introduced into a side chain bonded to the polyurethane chain.

[0039] When the polyurethane resin has a carboxy group, the acid value of the polyurethane resin is preferably 4.0 mgKOH / g or more and 40 mgKOH / g or less. By setting the acid value of the polyurethane resin in the above range, the crosslinking density with the crosslinking agent can be optimized, and the storage modulus and loss tangent of the adhesive layer 14 at 100°C and 120°C can be easily kept within a suitable range. The acid value is more preferably 6.0 mgKOH / g or more and 8.0 mgKOH / g or more. On the other hand, it is more preferably 30 mgKOH / g or less and 20 mgKOH / g or less.

[0040] (Crosslinking agent) As described above, the adhesive composition constituting the adhesive layer 14 contains a crosslinking agent in addition to a polyurethane resin. The crosslinking agent is a compound having two or more reactive groups in one molecule that can react with the reactive functional group of the polyurethane resin, and forms crosslinks between molecular chains of the polyurethane resin after the adhesive composition is heated. Examples of the crosslinking agent include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, aziridine-based crosslinking agents, metal chelate-type crosslinking agents, melamine resin-based crosslinking agents, and urea resin-based crosslinking agents. Among these, epoxy-based crosslinking agents are more preferable from the viewpoints of adhesion, heat resistance, and the like.

[0041] The epoxy crosslinking agent is a compound having two or more epoxy groups as reactive groups in one molecule. The epoxy crosslinking agent may be used alone or in combination of two or more kinds.

[0042] Examples of epoxy crosslinking agents include bisphenol A type epoxy resins, epichlorohydrin type epoxy resins, ethylene glycidyl ether, N,N,N',N'-tetrakis(2,3-epoxypropyl)-1,4-phenylenediamine, N,N,N',N'-tetrakis(oxiran-2-ylmethyl)-4,4'-methylenebisaniline, N,N-diglycidyl-4-(glycidyloxy)aniline, N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,1,2,2-tetrakis(3-glycidyloxyphenyl)ethane, diglycidylaniline, diamine glycidylamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, and neopentyl glycol diglycidyl ether. Examples of the epoxy crosslinking agents include ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, sorbitol polyglycidyl ether, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, glycerin diglycidyl ether, glycerin triglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, adipic acid diglycidyl ester, o-phthalic acid diglycidyl ester, triglycidyl-tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, and bisphenol-S-diglycidyl ether. Among these epoxy crosslinking agents, polyfunctional epoxy crosslinking agents having 3 to 5 epoxy groups in one molecule are preferred from the viewpoints of high adhesion and heat resistance.

[0043] The crosslinking agent in the adhesive composition is preferably a liquid having a viscosity of 500 mPa·s or more at 25°C, or a solid having a softening point of 100°C or less. The molecular weight of the crosslinking agent in the adhesive composition is preferably 200 or more, more preferably 400 or more, and even more preferably 600 or more. On the other hand, the molecular weight is preferably 10,000 or less, more preferably 5,000 or less, and even more preferably 1,000 or less. The functional group equivalent of the reactive group of the crosslinking agent in the adhesive composition (epoxy equivalent in the case of an epoxy-based crosslinking agent) is preferably 50 g / eq or more, more preferably 100 g / eq or more, and even more preferably 150 g / eq or more. On the other hand, the functional group equivalent is preferably 1,000 g / eq or less, more preferably 600 g / eq or less, even more preferably 400 g / eq or less, and particularly preferably 250 g / eq. If the molecular weight and reactive group content of the crosslinking agent are within the above ranges, good adhesion to the MEA and moist heat resistance can be obtained.

[0044] The content of the crosslinking agent in the adhesive composition is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, even more preferably 5 parts by mass or more, and particularly preferably 10 parts by mass or more, per 100 parts by mass of the polyurethane resin. Meanwhile, the content is preferably 30 parts by mass or less, more preferably 25 parts by mass or less, and even more preferably 20 parts by mass or less. When the content of the crosslinking agent (B) is within the above range, good adhesion to the MEA and good resistance to moist heat can be obtained.

[0045] In the adhesive composition, the ratio (b / a) of the molar amount (a) of the reactive functional group of the polyurethane resin, such as a carboxyl group, to the molar amount (b) of the reactive group of the crosslinking agent, such as an epoxy group of the epoxy crosslinking agent, is preferably 1.0 or more, more preferably 1.1 or more, and even more preferably 1.3 or more. On the other hand, the molar ratio is preferably 10.0 or less, more preferably 8.0 or less, and even more preferably 7.0 or less. If the molar ratio is 1.0 or more, sufficient crosslinking density can be obtained and the storage modulus can be made suitable. If the molar ratio is 10.0 or less, the adhesive layer 14 has high adhesion to the adherend, peeling and the like are effectively suppressed, and durability is improved.

[0046] (Other additives) In addition to the polyurethane resin and the crosslinking agent, other additives may be blended into the adhesive composition. Examples of other additives include crosslinking accelerators, crosslinking retarders, fillers, plasticizers, softeners, peeling aids, silane coupling agents, dyes, pigments, dyes, fluorescent brighteners, antistatic agents, wetting agents, surfactants, thickeners, antifungal agents, preservatives, oxygen absorbers, ultraviolet absorbers, antioxidants, near-infrared absorbers, water-soluble quenching agents, fragrances, metal deactivators, nucleating agents, alkylating agents, flame retardants, lubricants, processing aids, etc. These are appropriately selected and blended for use depending on the application and purpose of the adhesive sheet 10, that is, the specific type and configuration of the MEA to which the adhesive sheet 10 is applied, the usage environment, etc.

[0047] Among the above additives, the filler is blended for the purpose of improving the resistance to moist heat, adjusting the modulus of elasticity, making the adhesive sheet 10 tack-free and improving the removal of attached foreign matter, etc. The filler may be either an inorganic filler or an organic filler. Examples of inorganic fillers include inorganic particles such as silica, alumina, calcium carbonate, talc, and clay. Examples of such resin fillers include resin particles made of resins such as (meth)acrylic resin, styrene resin, styrene-(meth)acrylic resin, urethane resin, polyamide resin, silicone resin, epoxy resin, phenolic resin, polyethylene resin, and cellulose.

[0048] (Method of manufacturing adhesive composition) The adhesive composition can be produced by mixing a polyurethane resin, a crosslinking agent, and other additives that are used as necessary. The adhesive composition may be a solution that is diluted with an appropriate solvent to have a viscosity suitable for forming the adhesive layer 14.

[0049] Examples of the solvent include aliphatic hydrocarbons such as hexane and heptane; aromatic hydrocarbons such as toluene and xylene; halogenated hydrocarbons such as methylene chloride and ethylene chloride; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, 2-pentanone, isophorone, and cyclohexanone; esters such as ethyl acetate, propyl acetate, isopropyl acetate, and butyl acetate; cellosolve-based solvents such as ethyl cellosolve; and alcohol-based solvents such as ethanol, isopropyl alcohol, n-butyl alcohol, ethylene glycol monomethyl ether, ethylene glycol monoisopropyl ether, propylene glycol monomethyl ether, and diethylene glycol monobutyl ether. One of these solvents may be used alone, or two or more may be mixed and used. The amount of the solvent used may be appropriately adjusted so that the adhesive composition has a viscosity suitable for coating, and is not particularly limited. From the viewpoint of coatability, the amount is preferably 1% by mass to 90% by mass, more preferably 10% by mass to 80% by mass, and even more preferably 20% by mass to 70% by mass.

[0050] (Method of manufacturing adhesive sheet) The adhesive sheet 10 of this embodiment can be formed by (1) a method in which an adhesive composition is directly applied onto one side of a base film 12, followed by a drying and curing process by heat treatment, and optionally aging, or (2) a method in which an adhesive composition is applied onto the surface of a release film, heat treated, transferred onto one side of the base film 12, and optionally aged. Of these, the method (1) in which an adhesive composition is directly applied onto one side of the base film 12 is preferred from the viewpoint of adhesion to the base material.

[0051] For coating the adhesive composition, various coating methods such as reverse gravure coating, direct gravure coating, die coating, bar coating, wire bar coating, roll coating, spin coating, dip coating, spray coating, knife coating, kiss coating, etc., and various printing methods such as inkjet printing, offset printing, screen printing, flexographic printing, etc., can be used. In addition, before coating the adhesive composition, the surface of the base film 12 may be subjected to surface treatment such as corona treatment, plasma treatment, hot air treatment, ozone treatment, ultraviolet treatment, etc. In particular, from the viewpoint of adhesion of the adhesive layer 14, it is preferable to perform corona treatment.

[0052] The drying and curing steps are not particularly limited as long as they can remove the solvent and the like used in the adhesive composition and can cure it, but are preferably carried out at a temperature of 60° C. to 200° C. for about 20 to 300 seconds. In particular, the drying temperature is preferably 120° C. to 130° C. The cured state of the adhesive composition is preferably left in such a way that some uncured material remains (semi-cured state).

[0053] The curing may be carried out, for example, for about 3 to 20 days at 40° C. to 80° C., and preferably for about 4 to 7 days at 60° C. By carrying out the above drying and curing steps and, if necessary, a curing step, the gel fraction of the adhesive layer 14 can be set within a predetermined range, and strong adhesion to the MEA can be achieved in a short bonding step.

[0054] The adhesive sheet 10 may have a release sheet on the surface of the adhesive layer 14 until it is used. The release sheet is used as a protective material for the adhesive layer 14, and is peeled off when the adhesive sheet of the present invention is applied to an adherend. Examples of the release sheet include paper such as glassine paper, coated paper, and laminated paper, and various plastic sheets coated with a release agent such as silicone resin. In addition, when the adhesive layer 14 does not have adhesiveness, a sheet having adhesiveness on at least one side may be used. As the plastic sheet used for the release sheet, those listed as the base film 12 can be appropriately used. There is no particular limitation on the thickness of the release sheet, but it is usually 10 μm to 150 μm.

[0055] (How to use the adhesive sheet) The adhesive sheet 10 can be used as a sub-gasket for the MEA. In this case, the surface of the adhesive sheet 10 on which the adhesive layer 14 is formed is brought into contact with the MEA, and the adhesive sheet 10 and the MEA are laminated. At this time, the adhesive sheet 10 is positioned so that the solid electrolyte membrane of the MEA faces the opening W1 of the adhesive sheet 10. Then, the adhesive sheet 10 is heated while applying pressure in a direction to press the adhesive sheet 10 against the MEA, and the adhesive layer 14 is bonded to the MEA. Examples of the pressure are 0.5 to 10 MPa, the heating temperature is 130 to 170°C, and the pressurizing and heating time are 3 to 60 seconds. After the heat-pressure bonding process, the adhesive sheet 10 can be used in subsequent processes such as laminating power generating cells without undergoing a hardening process such as heat treatment or aging.

[0056] <Other embodiments> FIG. 2 is a perspective view of an adhesive sheet 20 according to a second embodiment of the present invention. As shown in FIG. 2, the adhesive sheet 20 according to the second embodiment of the present invention has a second base film 16 in addition to the base film 12 and the adhesive layer 14 formed on the surface of the base film 12. The second base film 16 is provided on the surface of the adhesive layer 14 opposite to the surface on which the base film 12 is provided. The second base film 16 covers the surface of the adhesive layer 14 in a portion of the adhesive layer 14 that does not contact the MEA. That is, the second base film 16 is provided with an exposure opening W2 as a through hole larger than the opening W1 provided in the base film 12 and the adhesive layer 14 (including the entire opening W1 inside). Then, inside the exposure opening W2, the adhesive layer 14 in a portion surrounding the opening W1 is exposed. The adhesive layer 14 exposed inside this exposure opening W2 comes into contact with the MEA placed on the adhesive sheet 20 and is bonded to the MEA. In the adhesive sheet of the present embodiment, the adhesive layer 14 is not exposed on the outermost surface except for the portion inside the exposed opening W2 that is bonded to the MEA, so that adhesion of foreign matter to the adhesive layer 14 can be suppressed and any foreign matter that has adhered can be easily removed. Other configurations of the adhesive sheet 20 according to the second embodiment can be similar to those of the adhesive sheet 10 according to the first embodiment described above.

[0057] The second base film 16, like the base film 12, may be made of a polyester resin such as polyethylene terephthalate resin, polybutylene terephthalate resin, polyethylene naphthalate resin, or liquid crystal polyester, a polycarbonate resin, a poly(meth)acrylate resin, a polystyrene resin, a polyamide resin, a polyphthalamide resin, a polyimide resin, a polyacrylonitrile resin, a polypropylene resin, a polyethylene resin, a polyolefin resin such as a polycycloolefin resin or a cycloolefin copolymer resin, a polyphenylene sulfide resin, a polyvinyl chloride resin, a polyvinylidene chloride resin, a polyvinyl alcohol resin, a polyvinylidene fluoride resin, a fluorine resin, a silicone resin, a polysulfone resin, a polyethersulfone resin, a polyetheretherketone resin, or a polyarylate resin, etc. The polymer material of the second base film 16 may be made of only one of these, or may be made of a combination of two or more of them by lamination or the like. Among these, from the viewpoints of heat resistance, mechanical properties, and the like, polyarylate, polyethylene terephthalate, polyethylene naphthalate, polyamide, polyimide, polyphenylene sulfide, polysulfone, polyethersulfone, polyetheretherketone, and polyarylate resins are preferred, and it is preferable that the second base film 16 is made of at least one resin material selected from the group consisting of these resins.

[0058] In the adhesive sheets 10, 20 according to the first and second embodiments described above, the adhesive layer 14 (and the second base film 16) is provided only on one side of the base film 12, but the adhesive layer 14 (and the second base film 16) may be provided on both sides of the base film 12. In addition, by using the base film 12 and the second base film 16, the adhesive sheet becomes easier to handle and operations such as lamination with the MEA are also easier to perform, but the adhesive sheet may be formed only from the adhesive layer 14 as a self-supporting adhesive film without using the base film 12 and the second base film 16. Furthermore, in the above, the adhesive sheets 10, 20 are formed into a shape having an opening W1 and are formed into a form of a subgasket to be used by laminating with the MEA, but the adhesive sheet according to the embodiment of the present invention does not necessarily have to constitute a subgasket, and can be formed into a shape according to the application and used at a place in the fuel cell where sealing is required. EXAMPLES

[0059] The present invention will be described in detail below using examples and comparative examples. Note that the present invention is not limited to these examples. Unless otherwise specified, each step of preparing and evaluating a sample is carried out in air at room temperature.

[0060] <Sample preparation> Example 1 Preparation of adhesive composition The following polyurethane resins <1> (Toyochem "VA-9302") for 100 parts by mass of solid content, the following epoxy crosslinking agent <1> An adhesive composition was prepared by adding 6.0 parts by mass (solid content) of TOYOCHEM's "HD-901" and then adding toluene so that the solid content concentration became 19% by mass.

[0061] - Preparation of adhesive sheet The adhesive composition was applied to one side of a polyethylene naphthalate (PEN) film ("Teonex Q51" manufactured by Toyobo) using a Baker-type film applicator so that the thickness after drying would be 10 μm, and heated at 150°C for 3 minutes. After that, the release surface of a release film ("HY-S10" manufactured by Higashiyama Film, a silicone-based PET release film, thickness 25 μm) was attached to the side of the adhesive composition that was not covered by the PEN film. After this, the film was aged at 60°C for 6 days to produce an adhesive sheet.

[0062] (Examples 2 to 11, Comparative Examples 1 to 3) The formulations of the adhesive compositions and the aging conditions were as shown in Table 1, and adhesive sheets were produced in the same manner as in Example 1 above.

[0063] The materials used in producing the samples of Examples 1 to 11 and Comparative Examples 1 to 3 are as follows. ·resin <1> VA-9302 (manufactured by Toyochem, polyurethane resin, solvent: toluene / isopropanol, solids concentration: 25.5% by mass, reactive functional group: carboxy group, acid value: 10 mg KOH / g) ·resin <2> VA-9320 (manufactured by Toyochem, polyurethane resin, solvent: toluene / isopropanol, solids concentration: 25% by weight, reactive functional group: carboxy group, acid value: 10 mg KOH / g) ·resin <3> : Aronmighty AS-350 (manufactured by Toagosei, modified epoxy resin, solvent: toluene, methanol, ethylene glycol monomethyl ether, dimethylformamide, xylene, diethylene glycol dimethyl ether, solids concentration: 30% by mass) ·resin <4> VA-9315 (manufactured by Toyochem, polyurethane resin, solvent: toluene / isopropanol, solids concentration: 22.0% by mass, reactive functional group: carboxy group, acid value: 10 mg KOH / g) ·resin <5> VA-9315H1 (manufactured by Toyochem, polyurethane resin, solvent: toluene / isopropanol, solids concentration: 22.2% by mass, reactive functional group: carboxy group, acid value: 10 mg KOH / g) ·resin <6> VA-9315H2 (manufactured by Toyochem, polyurethane resin, solvent: toluene / isopropanol, solids concentration: 21.3% by mass, reactive functional group: carboxy group, acid value: 10 mg KOH / g) Crosslinking agent <1> : HD-901 (manufactured by Toyochem, tetrafunctional epoxy resin, solvent: toluene-methyl ethyl ketone, solid content concentration: 50% by mass, epoxy equivalent: 200g / eq, softening point: 92℃) Crosslinking agent <2> : jER604 (Mitsubishi Chemical, tetrafunctional epoxy resin, solid content: 100% by mass, epoxy equivalent: 120 g / eq, viscosity at 25°C: 8000 mPa s) Crosslinking agent <3> : jER630 (Mitsubishi Chemical, trifunctional epoxy resin, solid content: 100% by mass, epoxy equivalent: 98 g / eq, viscosity at 25°C: 800 mPa s) Crosslinking agent <4> : TETRAD-C (manufactured by Mitsubishi Gas Chemical, tetrafunctional epoxy resin, solid content: 100% by mass, epoxy equivalent: 103 g / eq, viscosity at 25°C: 2300 mPa s)

[0064] <Evaluation method> (storage modulus, glass transition temperature) Each adhesive composition prepared above was applied to the release surface of a release film and dried at 150°C for 3 minutes. The adhesive composition was further applied onto the adhesive layer, and the process of drying at 150°C for 3 minutes was repeated to laminate until the thickness reached 0.5 mm. Then, aging was performed under predetermined conditions to prepare a test sample. After peeling off the release film from this sample, the shear storage modulus (G') was measured from -40°C to 150°C using a viscoelasticity measuring device (TA Instrument, Discovery HR-2). The measurement conditions were shear mode, geometry: 8 mm diameter parallel plate, axial force: 1.0 N, normal load: 1.0 N, frequency: 1 Hz, and heating rate: 5°C / min. Additionally, the loss modulus (G") was also measured, and the temperature at which the loss tangent (tan δ) calculated as the value (G" / G') obtained by dividing the loss modulus (G") by the storage modulus (G') was maximized was determined as the glass transition temperature.

[0065] (Gel fraction) The mass W1 of a wire mesh (400 mesh) cut to a width of 50 mm and a length of 120 mm was measured. 0.1 g of the adhesive layer was taken from the adhesive sheet prepared above, wrapped in a wire mesh to prepare a test piece, and the mass W2 of this test piece was measured. The test piece was placed in a glass bottle, 40 g of toluene was poured in, and the test piece was shaken lightly, and then left to stand at room temperature (25 ° C) for 76 hours. After standing, the test piece was removed from the glass bottle and left at room temperature for 12 hours, and then dried in a vacuum oven at 100 ° C for 4 hours. The dried test piece was cooled to room temperature, the mass W3 was measured, and the gel fraction was calculated using the following formula. Gel fraction (mass%) = ((W3-W1) / (W2-W1)) x 100

[0066] (Thickness) The total thickness of the entire adhesive sheet was measured using a thickness measuring device (manufactured by Tester Sangyo, "TH-104"), and the thickness of the adhesive layer was determined by subtracting the thicknesses of the base film and release film from this total thickness.

[0067] (Initial peel strength) The release sheet of the adhesive sheet was peeled off from the adhesive layer, and a solid polymer electrolyte membrane (DuPont, "Nafion PFSA NR-212", thickness: 50.8 μm) was placed on the surface of the adhesive layer, and the membrane was pressed using a small heat press machine "H400-15" manufactured by AS ONE to prepare a test sample.

[0068] The prepared test sample was stored at room temperature (23°C) for 30 minutes, then cut into a size of 25 mm wide and 150 mm long, and the peel force was measured at a peel speed of 50 mm / min and a peel angle of 180° using a Shimadzu Corporation precision universal testing machine "AUTOGRAPH (registered trademark) AGS-1kNX, 50N load cell" according to the method of JIS Z 0237 (2009). If the peel force is approximately 1N / 25mm, it is considered to be sufficiently large as the initial peel force and adhesion has been completed.

[0069] (Boiling test) Test samples were prepared in the same manner as the samples used to evaluate the initial peel strength, and five pieces were cut into pieces 50 mm wide and 50 mm long. These samples were immersed in boiling water at 98°C or higher for 270 hours, and the degree of peeling of the adhesive layer was visually evaluated according to the following four-point scale. ⊚: No lifting, peeling or voids on all five sheets. ○: Less than 2 out of 5 samples had lifting or peeling less than 1 mm at the edge, but the other samples had no lifting, peeling, or voids. Lifting, peeling, and voids less than 1 mm in length are acceptable for the adhesion state of MAE subgaskets in high temperature and high humidity environments. △: Three or more of the five samples had lifting, peeling, or voids less than 1 mm long at the edge, but none had lifting or peeling of 1 mm or more long. None of the examples or comparative examples were classified into this stage. ×: Lifting, peeling, or voids having a length of 1 mm or more were observed in one or more of the five samples.

[0070] <Test Results> The composition of each sample and the evaluation results are shown in Table 1. For the blending composition of the adhesive composition, the content of each component is shown in parts by mass.

[0071] [Table 1]

[0072] In Examples 1 to 11, the adhesive layer of the thermosetting adhesive sheet was formed from a cured product of an adhesive composition containing a polyurethane resin having a reactive functional group and a crosslinking agent, the gel fraction of the adhesive layer was 60 mass% or more, and the storage modulus at 100 ° C. (G' 100 ) is 5.0 × 10 4 Pa or more 1.0×10 8 The storage modulus (G') at 100°C is 100 ) versus storage modulus at 120°C (G' 120) is 0.5 or less. Correspondingly, the adhesive sheet has excellent storage stability, and as shown in the evaluation result of the initial peeling force, adhesion can be completed by heating and pressing in a short time, and as shown in the evaluation result of the appearance after boiling, adhesion defects such as lifting, peeling, and voids can be suppressed even when placed in a high-temperature, high-humidity environment. Among them, in Examples 1, 2, and 4 to 6, in which the gel fraction of the adhesive layer is 90 mass % or more and the decrease rate of the storage modulus is 0.2 or less, a particularly large initial peeling force and high resistance to a high-humidity, high-temperature environment are obtained. In Examples 8 to 11, in which the glass transition temperature is 50°C or more, high resistance to a high-temperature, high-humidity environment is also obtained.

[0073] In Comparative Examples 1 and 2, the decrease in storage modulus exceeded 0.5, and peeling of the adhesive layer occurred in the boiling test. 100 is 5.0×10 4 The initial peel strength was not measured because the adhesion was poor and the gel fraction was less than 60% by mass. 100 is 1.0×10 8 Corresponding to the pressure exceeding Pa, the adhesive layer had low adhesion and could not be adhered to the solid polymer electrolyte membrane.

[0074] Although the embodiments of the present invention have been described above, the present invention is not limited to the above embodiments, and various modifications can be made without departing from the spirit and scope of the present invention. [Explanation of symbols]

[0075] 10 Adhesive sheet 12 Base film 14 Adhesive layer 16 Second base film W1 opening W2 exposure port

Claims

1. A thermosetting adhesive sheet used to seal the periphery of an electrolyte membrane electrode assembly in which electrodes are disposed on both sides of a solid polymer electrolyte membrane of a fuel cell, The adhesive layer is formed from a cured product of an adhesive composition containing a polyurethane resin having a carboxy group as a reactive functional group and a multifunctional epoxy crosslinking agent, The adhesive layer has a gel fraction of 70% by mass or more and 96% by mass or less, Storage modulus at 100°C (G' 100 ) is 5.0 x 10 4 Pa or more and 2.2 × 10 6 Pa or less, Storage modulus at 100°C (G' 100 Storage modulus at 120° C. (G′ 120 ) is 0.5 or less; The thermosetting adhesive sheet is pressure-bonded to Nafion (registered trademark) constituting the solid polymer electrolyte membrane.

2. 2. The thermosetting adhesive sheet according to claim 1, wherein the adhesive layer has a glass transition temperature of -10°C or higher and 100°C or lower.

3. 3. The thermosetting adhesive sheet according to claim 2, wherein the adhesive layer has a glass transition temperature of 50° C. or higher.

4. 4. The thermosetting adhesive sheet according to claim 1, wherein the ratio (b / a) of the molar amount (a) of the carboxyl group of the polyurethane resin to the molar amount (b) of the epoxy group of the polyfunctional epoxy crosslinking agent is 1.0 or more and 10.0 or less.

5. The adhesive layer is formed on one surface of a base film, The thermosetting adhesive sheet according to any one of claims 1 to 4, characterized in that the base film is a film composed of at least one resin material selected from the group consisting of polyarylate, polyethylene terephthalate, polyethylene naphthalate, polyamide, polyimide, polyphenylene sulfide, polysulfone, polyethersulfone, polyetheretherketone, and polyarylate.

6. the thermosetting adhesive sheet further has a second base film on a surface of the adhesive layer opposite to the surface on which the base film is provided, The thermosetting adhesive sheet according to claim 5, characterized in that the second base film is a film composed of at least one resin material selected from the group consisting of polyarylate, polyethylene terephthalate, polyethylene naphthalate, polyamide, polyimide, polyphenylene sulfide, polysulfone, polyethersulfone, polyetheretherketone, and polyarylate.

7. A subgasket for a fuel cell, comprising the thermosetting adhesive sheet according to claim 5 or 6.

Citation Information

Patent Citations

  • Natural rubber-based adhesive composition and method for suppressing yellowing of coated material

    JP2007262230A

  • Liquid resin composition and finished article

    JP2014051621A

  • Adhesive resin composition, and adhesive sheet

    JP2015017237A

  • Frame-attached electrolyte membrane-electrode structure and fuel battery

    JP2021027029A

  • Hot-melt adhesive sheet

    WO2019216402A1

Cited By

  • Adhesive sheets and combinations of adhesive sheets

    JP2026120958A

  • Adhesive agent laminate, adhesive sheet, and combination of adhesive sheets

    WO2026150629A1